Impact of the African Continental Free Trade Agreement (ALECA) on Exports - Diop, Alle Nar; Sene, Seydina Ousmane (International Journal of Economics and Financial Issues, 2019)
The objective of this article was to measure the impact of trade liberalization on intra-African trade in general and in particular on trade between WAEMU countries and Africa. The use of ex-ante evaluation indicators made it possible to highlight the tendency of African and UEMOA countries to trade with one another. The analysis of these indicators has also highlighted the low diversification and high concentration of exports on commodities but also the introversion of trade of African countries and those of UEMOA. To quantify the impact of trade liberalization on African countries and UEMOA, the structural gravity model of Anderson and Van Wincoop (2003) is used for trade analysis because data are widely available. The estimation of the model by Heckman (1979) method allowed us to show that when the tariffs imposed on the export of commodities are low, they encourage exports and make the goods available to foreign consumers. Restrictions on cross-border investment can limit both inflows and outflows, reducing markets and growth and export opportunities. A restriction of capital movements through the exchange rate contributes to the decline in exports. The free movement of populations leads to an increase in exports. Keywords: Exchange, Gravity, Exportation JEL Classifications: E, F, F1, F2, F3, F4 DOI: https://doi.org/10.32479/ijefi.7594